Presence of adenylate cyclase activity in Golgi and other fractions from rat liver. II. Cytochemical localization within Golgi and ER membranes (The Rockefeller University Press, 1976)
The presence of adenylate cyclase (AC) in liver Golgi and microsomal fractions from ethanol-treated rats was tested cytochemically using 5'- adenylyl imidodiphosphate (AMP-PNP) lead phosphate method. Parallel biochemical assays showed that rat liver Golgi AC was only partially inhibited by lead: in the presence of 1 mM Pb++ 80% of the enzyme was preserved, while when 2 mM Pb++ was used 25% remained. No cAMP was formed when the AMP-PNP medium was incubated in the presence of 1 or 2 mM Pb++ but in the absence of cell fractions, indicating that at these concentrations Pb++ does not cause the nonenzymatic hydrolysis of AMP- PNP. Therefore, the reaction product observed by cytochemical localization is not due to the nonenzymatic hydrolysis of AMP-PNP by Pb++. In Golgi subfractions, lead phosphate reaction product was widely distributed among Golgi elements: it was seen in association with the majority of the very low density lipoprotein-filled secretory droplets which predominated in the two lightest Golgi fractions (GF1 and GF2) as well as within the majority of the cisternae found in the heaviest Golgi fraction (GF3). In the latter, reaction product was heaviest along the dilated peripheral rims of the cisternae. In all cases, the reaction product was localized to the outside or cytoplasmic face of the Golgi membranes. When microsomes were incubated cytochemically for AC, deposits were found on the cytoplasmic surface of smooth endoplasmic reticulum (ER) membranes, but none were observed on rough ER membranes. The results confirm the biochemical data reported previously indicating the presence of AC in Golgi and smooth microsomal fractions from rat liver and further demonstrate that the activity is indeed indigenous to Golgi elements and not due to plasma membrane contaminants. They also indicate that AC is widely distributed among Golgi and smooth ER elements. Thus, AC is not restricted in its distribution to plasma membranes as usually assumed.